Global trends and health inequalities in mental disorders among older adults: a comprehensive analysis using global burden of disease 2021 data - Chen, Ying; Dong, Xiao; Xu, Wenxing; Long, Yudan; Liu, Kai (Frontiers in Public Health, 2025)
ObjectiveThis study aims to analyze global trends and health inequalities in mental disorders among older adults (≥60 years) using Global Burden of Disease (GBD) 2021 data, with a focus on informing equity-focused public health strategies to address disparities in burden and access to care.MethodsUsing GBD 2021 data, we examined mental disorders in adults ≥60 across 204 countries (1990–2021). We calculated age-standardized incidence (ASIR) and disability-adjusted life years (DALYs) rates and estimated annual percentage change (EAPC). Bayesian Age-Period-Cohort modeling and frontier analysis assessed trends and projections. Analyses used R (v4.4.2) and JD_GBDR software.FindingsIn 2021, there were 74.9 million (95%UI: 59.8–94.2) new mental disorder cases among older adults globally, with an ASIR of 6,867.6 per 100,000. ASIR remained stable since 1990 (EAPC: 0.01), but varied regionally from 13,024.1 (Central Sub-Saharan Africa) to 4,643.9 (Oceania). The age-standardized DALY rate (ASDR) was 2,095.4 per 100,000, highest in low-SDI regions (2,423.9) and lowest in high-SDI regions (1,934.2). Females had higher ASIR (7,483.7 vs. 5,181.6) and ASDR (2,198.3 vs. 1,760.2) than males, with male DALYs increasing (EAPC: 0.07). By 2035, ASDR is projected to rise to 2,494.5, with depressive and anxiety disorders predominant in high-SDI regions and schizophrenia more prevalent in low-SDI areas.ConclusionSignificant disparities persist, with low-SDI regions and women disproportionately affected. Targeted strategies should strengthen mental healthcare access, implement sex-specific interventions, and address aging-related challenges.